The median effective concentration of propofol in combination with different doses of esketamine during gastrointestinal endoscopy in adults - Feng, Miaomiao; Shi, Gaoxiang; Cui, Wenjing; Zhang, Ning; Xie, Qipeng; Zhang, Weiwei (Frontiers in Pharmacology, 2022)
Abstract We designed a four-arm randomized controlled trial to investigate the median effective concentration (EC50) of propofol in combination with different doses of esketamine inducing appropriate depth of anaesthesia during gastrointestinal endoscopy in adults. One hundred patients aged 18–65 years planning for gastrointestinal endoscopy were divided into four groups randomly: esketamine 0, 0.15, 0.25 and 0.5 mg/kg groups (n = 25). Propofol doses followed the Dixon and Massey up-and-down method with different starting between groups. The primary endpoint was the EC50 of propofol, Secondary outcomes included the cumulative dose of propofol, the duration of the procedure, recovery time, and adverse effects. The EC50 (median, 95% confidence interval) of propofol was significantly less in the esketamine 0.5 mg/kg group compared with the esketamine 0, 0.15, and 0.25 mg/kg groups [1.34 (1.15, 1.54) vs 3.48 (3.25, 3.71), 2.82 (2.58, 3.07), and 2.36 (2.11, 2.61), respectively; P<0.001]. The total dose of propofol (mean±SD) required for the whole procedure was significantly less in the esketamine 0.5 mg/kg group compared with the esketamine 0, 0.15, and 0.25 mg/kg groups [95.5±43.1 vs 277.4±49.0, 207.8±31.6, and 135.1± 27.7, respectively; P<0.001]. The recovery time was significantly longer in esketamine 0 and 0.5 mg/kg group compared with other two groups (p<0.001). More patients in the esketamine 0.5 mg/kg group experienced visual disturbance compared with the other groups (p=0.016). And the incidence of hypotension in the esketamine 0 mg/kg group after inducation was higher compared with other groups (p<0.001). In summary, The administration of esketamine significantly and dose-dependently reduced the dose of propofol required to accomplish procedures.